2019
DOI: 10.3390/su11226507
|View full text |Cite
|
Sign up to set email alerts
|

Tourism as a Factor of Regional Development: Community Perceptions and Potential Bank Support in the Kopaonik National Park (Serbia)

Abstract: This paper represents a case study examining perceptions about tourism and reactions of the local community and bank decision makers to its development. The survey method was applied to establish the community’s attitude towards the impact of tourism in different spheres of life in the Kopaonik National Park (Serbia). The sample of 195 adult respondents covered inhabitants of 16 communities located within the wider area of the national park. In parallel, the potential support of banks for tourism development w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 78 publications
(123 reference statements)
0
9
0
7
Order By: Relevance
“…Factors affecting the support of the local community in tourism development have been extensively researched in the literature. Factors such as community loyalty, personal attitudes, and perceived benefits from tourism can strongly influence local community support (Meyer et al, 2017;Brankov et al, 2019). While Doxey (1975) explains the interaction between local community and tourists in tourism destinations with irritation index and Butler (1980) with destination lifecycle models, they assume that there is a change in the attitudes of the local population, mainly due to the increase in the number of tourists (Szromek et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Factors affecting the support of the local community in tourism development have been extensively researched in the literature. Factors such as community loyalty, personal attitudes, and perceived benefits from tourism can strongly influence local community support (Meyer et al, 2017;Brankov et al, 2019). While Doxey (1975) explains the interaction between local community and tourists in tourism destinations with irritation index and Butler (1980) with destination lifecycle models, they assume that there is a change in the attitudes of the local population, mainly due to the increase in the number of tourists (Szromek et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…National park Kopaonik belongs to I category, i.e, to the protected area of the international , national, i.e, of extreme importance for the Republic of Serbia. The area of the National park Kopaonik is important from the aspect of preservation of biodiversity, particularly areas important for preservation of plant species -IPA area (Important Plant Areas), for preservation of diversity of birds IBA -(Important Birds Areas) and daily butterflies PBA-Prime Butterfly Areas [26] As [27], municipalities on the territory of the national park Kopaonik experienced drop in economic activities and consequentially a status of "extremely undeveloped unit of local self-government have allotted to them" with the degree of development below 60% in relation to the national average. Previous research suggested that that National park Kopaonik and its protected zone can be classified as neglected mountain areas, according to criteria of regional classification of rural areas in the EU.…”
Section: Description Of the Value Of The National Park Kopaonikmentioning
confidence: 99%
“…In order to develop tourism in sustainable ways, there should be an equal and appropriate development of socio-cultural, environmental, and economic aspects of a destination [90,94]. From the output of structural equation modeling (SEM), it is concluded that there is a perfect positive correlation among socio-cultural, environmental, economic, and sustainable tourism developments, as the value of the correlation coefficient "R" was above 0.9 in all cases.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%